Entinostat, a histone deacetylase inhibitor, enhances CAR-NK cell anti-tumor activity by sustaining CAR expression - Jo, Dong-Hyeon; Kaczmarek, Shelby; Khan, Abrar Ul Haq; Pervin, Jannat; Clark, Diana M.; Gadde, Suresh; Wang, Lisheng; McComb, Scott; Visram, Alissa; Lee, Seung-Hwan (Frontiers in Immunology, 2025)
Allogeneic natural killer (NK) cell therapy has demonstrated significant potential in cancer immunotherapy by harnessing NK cells to target malignancies. CD138-targeting chimeric antigen receptor (CAR)-engineered NK cells offer a promising therapeutic option for multiple myeloma (MM). However, sustaining CAR expression on CAR-NK cells during ex vivo expansion poses a challenge to developing effective immunotherapies. In this study, primary NK cells were isolated, cryopreserved, and modified to express anti-CD138 CARs through retroviral transduction. Histone deacetylase inhibitors (HDACi), particularly entinostat (ENT), were applied to enhance CAR expression stability in CAR-NK cells. Our findings indicate that ENT treatment significantly improves and maintains CAR expression, thereby enhancing the cytotoxic activity of CAR-NK cells against CD138-positive multiple myeloma cells. ENT-treated CAR-NK cells exhibited prolonged persistence and more significant tumor reduction in an MM tumor-bearing mouse model, highlighting the therapeutic potential of HDACi-treated CAR-NK cells. This study provides the first evidence that HDAC inhibitors can sustain CAR expression in CAR-NK cells in a promoter-dependent manner, potentially enhancing anti-tumor efficacy in multiple myeloma and underscoring the possible need for further clinical evaluation.